KONSEP DAN TEKNIK MANAIEMEN MUTU TERPADU - Pruba, Saut (UNIKA Santo Thomas, 2011)
Quality is a term that has diï¬‚ferent meanings to different people. Quality set out in this paper are the features and characteristics of the total of a product or service associated with its ability to satisï¬j the needs of the visible or disguised. The quality of the environment requires an establishment of TQM because quality can not be examined only in a product. In this paper also discussed the concept of the seven TQM: continuous improvement, Six Sigma, employee empowerment, benchmarking, just in time, the concept of Taguchi TQM techniques and knowledge. TQM is the seventh technique check sheet, scatter diagrams, cause-effect diagrams, Pareto charts, ï¬‚ow charts, histograms, and statistical process control.